The Effectiveness of Public Services of The Sorong City Education Office to The Community in Sorong City - Elvira Isir; Karmanis Karmanis; Tri Lestari Hadiati (Law and Justice research journal, 2026)
This study aims to analyze the effectiveness of the public services of the Sorong City Education Office for the community by examining the relationships among service effectiveness, community satisfaction, service accountability, and apparatus responsiveness. The research uses a mixed-methods approach: a quantitative component involving distributing questionnaires to 30 respondents, analyzed using descriptive statistics and correlation, and a qualitative component involving in-depth interviews with five main sources, analyzed using triangulation and thematic analysis. The results of the study show that the effectiveness of public services is in the good category, with a significant relationship between service effectiveness and community satisfaction, service accountability, and responsiveness of the apparatus. Apparatus responsiveness has the strongest relationship with service effectiveness, showing the importance of officer responsiveness in improving the quality of education services. The interview findings also show that education services have improved, though further progress is needed in service speed and information transparency. The study's findings confirm the relevance of public administration theory and service quality in explaining the performance of regional education services. The research is limited in the small number of respondents and its focus on a single agency. Therefore, further research is recommended to increase the sample size, involve several public service agencies, and use a more comprehensive analytical model.